Arah Pengembangan Biosistematika di Indonesia - Soenartono Adisoemarto; Yayuk R. Suhardjono (Universitas Gadjah Mada, 1997)
To be able to see general picture of organism diversity, including their interrelationships, biosystematics is applied. Usefulness of these interrelationships is related to the positions of each of the units, which can be determined only by biosystematics. However, not too many biosystematicist are aware of the usefulness of these interrelationships. To reveal the interrelationships and hierarchy restructurization of the grouping in needed. There are two approaches proposed to do the restructurization : through concept of biosystematics and through biosystematics units. The biosystematic units approach has been selected. In the short term program, identification of biosystematic categories with high priority is suggested to be selected as the units to be handled. ln this respect, it is relevant to the management of agricultural pests and weeds, especially on rice. Special efforts must be given to biotype development, seasonal forms, complex species, and indication of evolutionary tendency of important species. The lack of data and information on these aspects will hinder the roles and function of biosystematics. For long term program, the activities will be focused on the identification of groups and research aspects which support their biosystematic endeavour. The suggested high prioritized group is Pyralidae as rice pests, followed by soil insect of agricultural importance, fruit flies of the family Tephtritidae, and horticultural, plantation and wood pests. For health aspect, focusing on sibling and complex species is needed, especially on the vectors of malaria and dengue haemorrhagic fever. Short term program projection is the availability and adequacy of data for treatment in short period. For long term program the formulation for anticipating the impacts of the development on the selected groups. Both of these program projections are also needed by the educational institutions for planning and determining human resources needed for conducting the program.